Effects of dielectric barrier discharge (DBD) generated plasma on microbial reduction and quality parameters of fresh mackerel (Scomber scombrus) fillets. (December 2017) - Albertos, I.; Martín-Diana, A.B.; Cullen, P.J.; Tiwari, B.K.; Ojha, S.K.; Bourke, P.; Álvarez, C.; Rico, D.
Abstract: The effect of atmospheric cold plasma generated by a novel in-package dielectric barrier discharge (DBD) on microbial and quality parameters of mackerel fillets was investigated. DBD voltage (70 kV and 80 kV) and treatment time (1, 3 and 5 min) were studied. Within 24 h of DBD treatment, spoilage bacteria (total aerobic psychrotrophic, Pseudomonas and lactic acid bacteria) were significantly reduced. However, significant effects on lipid oxidation parameters (PV, Dienes) were observed for the treated samples. Both studied treatment factors, treatment voltage and time, significantly affected anti-microbial efficacy and lipid oxidation. Nevertheless, no changes in pH or colour (except for L*) were observed. These results suggest atmospheric cold plasma generated by DBD could be implemented as technology for fish processing, retaining product quality over its shelf life. However, further investigations are needed in order to implement this technology and to control and mitigate its limitations, mainly associated to increased oxidation. Industrial relevance: Cold atmospheric plasma (CAP) has gained attention as an emerging and non termal technology for decontamination of food. This technology has been used on fruits and vegetables successfully for the inactivation of food-borne pathogens. However, this technology has not been investigated in fish, being a highly persibale product. The use of dielectric barrier discharge (DBD) to produce cold plasma showed a potential industrial application at low cost and convenience. Cold plasma was found to be effective for reducing the main problem of oily fish quality such as the spoilage bacteria. However, this technology seems to accelerate oxidative pathways; for this reason, further studies to investigate the use of antioxidants in combination with cold plasma as "hurdle technology" to minimise this negative effect are suggested. Highlights: The effects of dielectric barrier discharge on mackerel fillets have been studied. Spoilage bacteria was significantly reduced as DBD voltaje-time increased. Lipid oxidation increased after DBD exposure. Colour parameters were not negatively affected by DBD. DBD caused changes in mobilised and extramyofibrillar water.